Balancing costs and benefits: a clinical perspective does not support a harm minimisation approach for self-injury outside of community settings - Pickard, Hanna (Journal of medical ethics, 2017)
Patrick Sullivan's emphasis on the importance of supporting autonomy and independence among vulnerable people who self-injure is fundamental to good clinical practice. Although people who self-injure typically experience overwhelming emotions and may be prone to impulsive behaviour, self-injury is nonetheless a choice and must accordingly be treated as such.1 In addition, patients who self-injure when not acutely mentally ill typically retain decision-making capacity in relation to self-injury.2 This is why some forms of harm minimisation, such as encouraging reflection, responsibility, safe cutting and where appropriate self-aftercare, are uncontroversial and already widely practised within community settings. The situation is different, however, with respect to both secure and non-secure inpatient settings. It is also different when we consider some of the other forms of harm minimisation that Sullivan advocates, namely the provision of self-harming instruments alongside education about anatomy and physiology.Sullivan does not distinguish secure and non-secure settings, but it is crucial to do so. In secure (forensic) inpatient settings, it is neither practical nor ethical to provide implements that can be used as weapons to any patient, for any reason. This would be to severely compromise staff and patient safety.In non-secure inpatient settings, patients are likely to be detained under the Mental Health Act. This raises the question of the grounds of detention. Typically, patients who self-injure are detained because they are judged to be currently at risk of life-endangering or life-changing injury. As Sullivan notes, it is not clinically or ethically appropriate to provide patients with the means to self-injure when they are in this state of mind. This means that the relevant inpatient population for which a harm minimisation approach could even be considered is relatively small: those who have a standing pattern of self-injury and who are detained on non-secure units for reasons other …